Current migraine management – patient acceptability and future approaches - Jean Schoenen; Arnaud Fumal (Neuropsychiatric Disease and Treatment, 2008)
Arnaud Fumal, Jean SchoenenDepartments of Neurology and Functional Neuroanatomy, Headache Research Unit, University of Liège, BelgiumAbstract: Despite its high prevalence and individual as well as societal burden, migraine remains underdiagnosed and undertreated. In recent years, the options for the management of migraine patients have greatly expanded. A number of drugs belonging to various pharmacological classes and deliverable by several routes are now available both for the acute and the preventive treatments of migraine. Nevertheless, disability and satisfaction remain low in many subjects because treatments are not accessible, not optimized, not effective, or simply not tolerated. There is thus still considerable room for better education, for more efficient therapies and for greater support from national health systems. In spite of useful internationally accepted guidelines, anti-migraine treatment has to be individually tailored to each patient taking into account the migraine subtype, the ensuing disability, the patient’s previous history and present expectations, and the co-morbid disorders. In this article we will summarize the phenotypic presentations of migraine and review recommendations for acute and preventive treatment, highlighting recent advances which are relevant for clinical practice in terms of both diagnosis and management.Keywords: migraine, disability, acute treatment, preventive treatment, management